Diabetic foot syndrome - severe complication of diabetes. Prophylaxis and care - Agata Pacholec (Kazimierz Wielki University, 2019)
Diabetes is an incurable metabolic disease whose neglect can lead to serious health complications. It is caused by a malfunction or insulin secretion by the pancreas. Diabetes is more and more often diagnosed in society and has become a disease of civilization. An increase in the incidence of diabetes is expected in the coming years. Inadequate treatment and inadequate control may cause hyperglycaemia, causing a number of consequences associated with an increase in glycaemia levels. Diabetic foot syndrome causes damage to peripheral nerves or vessels of the foot. Early detection of abnormalities allows to take appropriate action, therefore an important element of prevention of a person suffering from diabetes is foot control. Ignoring the symptoms may lead to the development of ulceration and infection or even at a later stage to amputation of the limb. The aim of the study is to present appropriate prophylaxis, care and treatment in the care of a patient with diabetic foot syndrome. The paper is based on a review of articles in reputable journals from the last few years.